1984
DOI: 10.1111/j.1755-3768.1984.tb05796.x
|View full text |Cite
|
Sign up to set email alerts
|

Some Factors Affecting the Intraocular Pressure Reduction After Argon Laser Trabeculoplasty in Open‐angle Glaucoma

Abstract: One hundred and thirty-five eyes in 120 patients with open-angle glaucoma were treated with argon laser trabeculoplasty and followed up for 6 months. The mean reduction in intraocular pressure in the whole material was 10.9 mmHg. 13.1 in eyes with capsular glaucoma and 7.2 in eyes with simple glaucoma. The possible influence of the degree of trabecular pigmentation, the pre-treatment intraocular pressure level and the presence of exfoliative material on the amount of pressure reduction was analysed. The presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
2

Year Published

1986
1986
2011
2011

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 10 publications
1
9
2
Order By: Relevance
“…Many studies have shown that IOP reduction is larger in exfoliation glaucoma than in POAG, 2,5,19,22,32,38 even after performing multivariate analyses to correct for differences in pre-ALT IOP between these two types of the disease. 3 There is no agreement as to whether the pressure-lowering effect of ALT is influenced by trabecular pigmentation or pigmentation grade, 3 -5,22,24,37,38 and we found no significant impact of either of those aspects in our investigation. However, it should be reiterated that the power of our study was low in this context, because only 7 patients had a non-pigmented trabecular meshwork.…”
Section: Discussioncontrasting
confidence: 54%
“…Many studies have shown that IOP reduction is larger in exfoliation glaucoma than in POAG, 2,5,19,22,32,38 even after performing multivariate analyses to correct for differences in pre-ALT IOP between these two types of the disease. 3 There is no agreement as to whether the pressure-lowering effect of ALT is influenced by trabecular pigmentation or pigmentation grade, 3 -5,22,24,37,38 and we found no significant impact of either of those aspects in our investigation. However, it should be reiterated that the power of our study was low in this context, because only 7 patients had a non-pigmented trabecular meshwork.…”
Section: Discussioncontrasting
confidence: 54%
“…For PALT this is in accordance with earlier findings (BergeH 1984(BergeH , 1986; Bergei 8c Svedbergh 1992).…”
Section: Discussionsupporting
confidence: 91%
“…ALT is known to reduce IOP more in CG than in SG (Pohjanpelto 1981;Tuulonen & Airaksinen 1983;Bergei 1984;Svedbergh & Shenvood 1985). The greater IOP reducing effect in CG compared to that in SG in this study was not significant two months after the fvst treatment.…”
Section: Discussionmentioning
confidence: 95%